IMPLEMENTATION OF FACE DETECTION AND RECOGNITION USING OPENCV FOR REAL-TIME BIOMETRIC AUTHENTICATION AND ATTENDANCE SYSTEMS - Tiwari, Prem Kumar; Rohan; Rinku; Kumar, Ashish (International journal of research - granthaalayah, 2024)
With the increasing reliance on technology for daily tasks, facial detection and recognition systems have emerged as critical tools in enhancing security and streamlining processes. These technologies are widely used in applications such as sorting photos in mobile galleries, unlocking devices, and even in national identification systems like Aadhaar, which accepts face images as biometric input for verification. This project explores the implementation of facial detection and recognition using OpenCV, an open-source computer vision library developed by Intel, and Python. The project demonstrates the practical application of these technologies on both Windows and macOS platforms, enabling real-time face detection and recognition using a webcam. The system is designed to identify faces that the script is trained to recognize, displaying their names in real-time.The main aim of the project is to develop a functional face recognition system that can be extended to larger applications, such as biometric attendance systems, which eliminate the need for time-consuming manual attendance processes. The implementation is built using Python 3.6.5, with the project providing documented code for various functionalities, including detecting faces in static images, capturing images for the training dataset, and training a classifier for recognizing faces. The face detection system is demonstrated through several algorithms and approaches that are discussed throughout the report.The broader application of facial recognition includes enhancing security measures, improving organizational processes, aiding marketing strategies, and advancing surveillance efforts. The technology's potential in surveillance can be particularly impactful, as it facilitates the identification of individuals with criminal records, including criminals and terrorists, thus contributing to national security. Additionally, facial recognition systems offer increased security for individuals by reducing the risk of hacking, as there are no passwords to steal or alter.This project also aims to improve the accuracy of facial recognition systems by reducing error rates in face detection. The ideal goal is to minimize intra-class variation while increasing inter-class variation, allowing for more accurate identification. Facial recognition software works by analyzing and comparing facial contours to uniquely identify or verify individuals, with its primary use in security-related applications. The project demonstrates the effective integration of facial recognition technology and provides valuable insights for further exploration and development in various fields, including security, surveillance, and personal identification.